The Impact of Green Finance, Energy and Sustainable Development Policies in BRICS Indonesia: A Robust Panel Data Econometric Modeling - Fattah, Sanusi; Hamrullah, Hamrullah; Nurbayani, Sri Undai; Fitrianti, Retno; Yusuf, Mohammad Amil (International Journal of Energy Economics and Policy, 2025)
Environmental change is reshaping the global economy. This study examines the relationship between green finance, sustainable development, and eco-friendly policies in BRICS countries and Indonesia from 1990 to 2023. We use panel data methods, including Driscoll-Kraay standard errors, FMOLS, DOLS, and Method of Moments Quantile Regression (MMQR), to assess the impacts of clean energy financing, environmental taxes, and renewable energy use on the Green finance index (GFI). Clean energy financing consistently drives green financial development across all models. Environmental taxation has mixed effects: It limits growth in less developed green markets (lower GFI quantiles), but its impact is less pronounced in more advanced markets. This study uniquely reveals non-linear, quantile-specific patterns, showing that the connection between finance, policy, and sustainability depends on a country’s stage of green market development. These results suggest that strategies should be tailored to individual needs. Focus on direct investment, and adjust fiscal tools based on market readiness to support a sustainable financial transition.